Effects of Transcranial Stimulation With Direct and Alternating Current on Resting-State Functional Connectivity: An Exploratory Study Simultaneously Combining Stimulation and Multiband Functional Magnetic Resonance Imaging - Mondino, Marine; Ghumman, Sukhmanjit; Gane, Claire; Renauld, Emmanuelle; Whittingstall, Kevin; Fecteau, Shirley (Frontiers in Human Neuroscience, 2020)
Background: Transcranial stimulation with direct (tDCS) and alternating current (tACS) has increasingly gained interest in various fields, from cognitive neuroscience to clinical investigations. Transcranial current stimulation used alone may modulate brain activity that consequently influences behaviours, but without providing information on potentially induced brain activity changes. Combination of transcranial current stimulation and fMRI may help to address this. This exploratory study investigated instantaneous and subsequent effects of tDCS and tACS on resting state functional connectivity in healthy adults. Methods: We conducted a randomized crossover study with fifteen healthy subjects receiving three stimulation conditions (tDCS, tACS, sham) on separate days. Stimulation was applied over the left and right dorsolateral prefrontal cortex for 30 min (1 mA). Resting-state functional connectivity of the targeted prefrontal areas were assessed before, during and after stimulation using multiband fMRI and using left and right dorsolateral prefrontal cortex as seeds. Results: Both tDCS and tACS increased resting state functional connectivity during and after the stimulation period, as compared to sham. tDCS-induced changes were observed between the left dorsolateral prefrontal cortex and bilateral parietal regions at the junction of the superior parietal and the inferior parietal lobules. tACS-induced changes were observed between the left dorsolateral prefrontal cortex and the right inferior parietal lobule. Conclusion: Overall, these results suggest that a single session with a low dose, 1mA, of tDCS or tACS can cause changes in fronto-parietal connectivity that occur rapidly, that is, within the first 15 minutes. Although exploratory, this work contributes to the discussion of the potential of transcranial current stimulation to modulate resting state networks and the interest of combining transcranial current stimulation with neuroimaging to identify these changes.